Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Do the factoring method
(3x-2)(x+3)
3x=2 X=-3
x=2/3
if we check
3x2+7x=6
3(2/3)2+7(2/3)=6
4/3+14/3=6
18/3=6
The x=2/3 is correct now lets see the x=-3
3x2+7x=6
3(-3)2+7(-3)=6
3(9)-21=6
27-21=6
6=6
so both x can be used in factoring
(3x-2)(x+3)
3x=2 X=-3
x=2/3
if we check
3x2+7x=6
3(2/3)2+7(2/3)=6
4/3+14/3=6
18/3=6
The x=2/3 is correct now lets see the x=-3
3x2+7x=6
3(-3)2+7(-3)=6
3(9)-21=6
27-21=6
6=6
so both x can be used in factoring
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.